2017
DOI: 10.12955/cbup.v5.973
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of the Corporate Image on the Competitiveness of Interior Design Enterprises

Abstract: Abstract:In striving to secure a competitive advantage in the market, companies endeavor to create a high level of trust and attachment of customers to the company. Building a positive image is a prerequisite for businesses to enhance their competitiveness. In this regard, the main objective of this paper is to identify measures of corporate image, competitiveness of enterprises, and the relationship between them. This paper uses statistical methods (variance, regression, and correlation analysis) to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…The creation of a general framework is very important to develop the study of corporate reputation and its effect on corporate performance. This research strengthens the results of Kyurova and Yaneva (2017) showing a strong correlation between corporate image and corporate competitiveness. In conclusion, corporate image is an important tool for realizing a sustainable market and achieving strong competitive advantage.…”
Section: Discussionsupporting
confidence: 89%
“…The creation of a general framework is very important to develop the study of corporate reputation and its effect on corporate performance. This research strengthens the results of Kyurova and Yaneva (2017) showing a strong correlation between corporate image and corporate competitiveness. In conclusion, corporate image is an important tool for realizing a sustainable market and achieving strong competitive advantage.…”
Section: Discussionsupporting
confidence: 89%
“…This can be attributed to the capital employed, firm age, labor cost and debt‐equity ratio. This findings is consistent with the studies of Adeniji et al (2015) and Kyurova and Yaneva (2017). Organizations are reasonably apprehensive about the management of their corporate social responsibility, which offers the company a befitting corporate image to maximize their potentials to ensure optimum performance.…”
Section: Discussionsupporting
confidence: 94%
“…Organizations are justifiably associated with handling their CSR, which offers the company a befitting corporate image to maximize their potentials and ensuring optimum performance. In view of this, there is a strong positive link existing among how individuals recognize an enterprise and the performance of the organization on the market (Adeniji et al, 2015; Kyurova & Yaneva, 2017). Corporate social responsibility increases financial performance through enhancing a company's relationships with its primary stakeholder groups, according to the core principle, (Saeed et al, 2023) in their recent study, CSR and financial performance nexus of financial institutions in Ghana, confirmed this position.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation